عقود التجارة الإلكترونية بين الفقه الإسلامي والقانون العماني :‏ ‏مجلس العقد أنموذجا /‏ - سعدي، مهنا بن راشد بن حمد (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2012)
The advent of the Internet has resulted in the emergence of electronic commerce and also the so-called electronic contract, where contracts and transactions are concluded with just a push of a button without direct meeting in person between the parties to the contract. This has resulted in patterns and modern methods in the contract which have not been practised before. It is therefore incumbent that the shari'ah explain the legitimacy of such contracts, and whether they are in line with Islamic law. This is what the researcher will attempt to answer by focusing on the place of conclusion of e-commerce contracts over the Internet, and whether the place is subject to the terms of the contract set forth in the traditional Islamic jurisprudence. The researcher will also make comparisons between Islamic jurisprudence and the law of the Electronic Transactions Act of Sultanate of Oman No. 69/2008. The researcher will depend on the analytical, deductive, and comparative study between the schools on Islamic jurisprudence, namely: Ibadi, Hanafi, Maliki, Shafi'i, and Hanbali, and analyse the outcomes of each school. An attempt is made to compare the case in Islamic jurisprudence and the electronic contract in the Electronic Transactions Act of Sultanate of Oman, No. 69/2008. The most important finding of the research is that there is no forbiddance or prohibition of electronic transactions in Islamic law, as long as these transactions are within the regulations of Islamic law, and does not intend harm or deceit, either to the seller, buyer or to others. The place of contract conclusion over the Internet varies according to the conditions of the contract. If it is contracted through audio or video where the contract is made at the present time but in different places, then it fulfills the specified conditions. However, if it is done through writing via e-mail or the like, where the contractual engagements occur at different time and place, the contract is subject to the law and conditions of two persons in absence, whether it is done through writing or through courier service. The time and place of conclusion contracts via the Internet do not restrict the contract process, as stated in Article (17) of the Electronic Transactions Act of Oman, and in consensus to Article (15) of the UNCITRAL Model, where there is no restriction in the time and place of conclusion of the contract. In commensuration with the reality of each country, we recommend an adjustment to Article (17) of the Electronic Transactions Act Oman in line with the reality of e-commerce in the Sultanate of Oman and the prevailing national legislation and practices.